ANALYSIS OF READING DIFFICULTIES OF HIGH GRADE STUDENTS OF SUKADAMAI SAREE STATE ELEMENTARY SCHOOL, ACEH BESAR DISTRICT - Nabila, Wulan; Hasniyati, Hasniyati; Yamin, M. (Universitas Syiah Kuala, 2024)
In learning activities, students often experience difficulties in the learning process because students have difficulty reading which occurs in high class students. Therefore, a study was conducted on the analysis of reading difficulties of high grade students of SD Negeri Sukadamai Saree, Aceh Besar Regency which aimed to find out what are the factors that cause reading difficulties that occur in these students. This understanding uses a qualitative approach type of case study. The subjects of the study were 3 high-class students. Data collection techniques are carried out through observation and interviews with students, teachers, parents, and close friends of students. Data analysis in this study uses the male and huberman model, namely data reduction, data presentation, and conclusions. The results of interview data analysis and observation of the subject that there are reading difficulties that occur in high grade students. From observation and interview activities, there are several factors that cause reading difficulties, namely internal factors in the form of intelligence levels, low learning motivation, lack of interest in reading activities and doing letter omissions, faltering, not recognizing letters and letter reversal. And external factors in the form of the state of the subject's family environment, the economic situation of parents and the lack of supporting media or reading materials. Therefore it can be concluded that learners have difficulty reading, so that during the process of learning activities they have difficulty and experience difficulties.